Проблема суффиксального усложнения: Н. В. Крушевский и современная русская дериватология - Крючкова, Ольга; Kryuchkova, Olga (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статье рассматривается вклад Н. В. Крушевского в изучение процессов суффиксального усложнения в русском языке, а также развитие высказанных ученым положений в современной русистике.The author considers the contribution of N. W. Kruszewski to the study of important problems of suffixal complexification in Russian: the derivational potential of this process, the place and role of duplicating complexi- fication (the compatibility of synonymous suffixes), the interpretation of morphemic complexes resulting from suffixal complexification (complex suffix; a sequence of formants; an integral formant dividable into morphemes). The article contains the analysis of modern state of the problem, controversial aspects of its study, and underlines its meaning to the development of both general theory of language and applied linguistics. The author also outlines the perspectives of the further study of processes of suffixal complexification.
The Problem of Suffixal Complexification: N. W. Kruszewski and the Modern Russian Derivatology
Keywords: русский язык; словообразование; редупликация; суффиксация; сложные суффиксы; Russian language; word-building; reduplication; addition of suffixes; complex suffixes